2004
DOI: 10.1590/s0034-72992004000500007
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopia do meato acústico interno pelo acesso retrolabiríntico

Abstract: O acesso direto à região do ângulo pontocerebelar pela via retrolabiríntica é seguro, entretanto, não permite a visão direta de todo o meato acústico interno (MAI) pela otomicroscopia. Os endoscópios podem ser utilizados na exploração do MAI por esta via. Objetivo: Nosso objetivo é avaliar a capacidade de inspeção do MAI com endoscópios de diferentes angulações. The retrolabyrinthine approach is a safe route to the cerebellopontine angle, which allows preservation of hearing and facial nerve function. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…A similar presigmoid retrolabyrinthine cadaveric study was performed by a Brazilian group who found that the 70° endoscope allowed for full view of the fundus of the IAC in 67.5% of specimens, the 30° endoscope allowed for full view of the fundus of the IAC in only 12.5% of specimens, and the 0° endoscope and microscope did not allow for visualization of the fundus 11 . The difference in results between their study and ours may be explained by the addition of endoscopically assisted drilling in our study.…”
Section: Discussionmentioning
confidence: 79%
“…A similar presigmoid retrolabyrinthine cadaveric study was performed by a Brazilian group who found that the 70° endoscope allowed for full view of the fundus of the IAC in 67.5% of specimens, the 30° endoscope allowed for full view of the fundus of the IAC in only 12.5% of specimens, and the 0° endoscope and microscope did not allow for visualization of the fundus 11 . The difference in results between their study and ours may be explained by the addition of endoscopically assisted drilling in our study.…”
Section: Discussionmentioning
confidence: 79%
“…The MD was first described by Prosper Ménière in 1861 with its clinical triad: dizziness, tinnitus, and hearing deafness, with or without aural fullness. 13 However, although some of these original aspects are still present in guidelines, a lot more has been discovered about this disease.…”
Section: Resultsmentioning
confidence: 99%
“…The MD commonly affects adults from 20 to 50 years 13 and is more likely to occur in women. 15 Both ears are affected with the same frequency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations